Seropositivity for Enterocytozoon bieneusi, Czech Republic - Sak, Bohumil; Kucerova, Zuzana; Kvac, Martin; Kvetonova, Dana; Rost, Michael; Secor, Evan W (Emerging infectious diseases, 2010)
To determine seropositivity for Enterocytozoon bieneusi in the Czech Republic, we tested 115 serum samples from various groups. We found that 20% from HIV-positive persons, 33% from persons with occupational exposure to animals, and 10% from healthy persons were positive by indirect immunofluorescence assay. Proteins of 32 kDa were detected in serum samples from seropositive persons.
Keywords: Enterocytozoon; HIV infekce; Česká republika; mikrosporidióza; surveillance populace; Czech Republic; HIV Infections; pracovní expozice; Population Surveillance; Microsporidiosis; lidé; dárci krve; Seroepidemiologic Studies; séroepidemiologické studie; Occupational Exposure; Humans; Blood Donors